2009
DOI: 10.1083/jcb.200901084
|View full text |Cite
|
Sign up to set email alerts
|

Different Rho GTPase–dependent signaling pathways initiate sequential steps in the consolidation of long-term potentiation

Abstract: The releasable factor adenosine blocks the formation of long-term potentiation (LTP). These experiments used this observation to uncover the synaptic processes that stabilize the potentiation effect. Brief adenosine infusion blocked stimulation-induced actin polymerization within dendritic spines along with LTP itself in control rat hippocampal slices but not in those pretreated with the actin filament stabilizer jasplakinolide. Adenosine also blocked activity-driven phosphorylation of synaptic cofilin but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
338
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 273 publications
(360 citation statements)
references
References 54 publications
(82 reference statements)
21
338
1
Order By: Relevance
“…Recent studies have shown that induction of plasticity at a single spine transiently lowers the plasticity threshold at adjacent spines (20). The mechanism underlying this phenomenon involves local spreading of signaling cascades from the activated spine to its neighbors, and some of these spreading signals are potent drivers of F-actin dynamics (24)(25)(26). Therefore, we asked if TBS2 induces F-actin polymerization in spines neighboring the synapses potentiated by TBS1.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that induction of plasticity at a single spine transiently lowers the plasticity threshold at adjacent spines (20). The mechanism underlying this phenomenon involves local spreading of signaling cascades from the activated spine to its neighbors, and some of these spreading signals are potent drivers of F-actin dynamics (24)(25)(26). Therefore, we asked if TBS2 induces F-actin polymerization in spines neighboring the synapses potentiated by TBS1.…”
Section: Resultsmentioning
confidence: 99%
“…One important caveat to note, however, is that total inhibition of Rho-GTPases might, in fact, not be an optimal strategy. Rho-GTPases play important physiological roles in normal synaptic functions, and their activities are essential for learning and memory, and for the establishment of LTP [48]. As a result, total inhibition may interfere with longterm signaling required for spine structural plasticity [49].…”
Section: Direct Modulation Of Rho-gtpases For Ad Treatmentmentioning
confidence: 99%
“…Actin is abundant in presynaptic terminals and postsynaptic spines (11), and numerous studies highlight the relevance of actin dynamics for postsynaptic plasticity (12). Pharmacologic studies and the subsynaptic distribution of actin filaments also suggest a role for actin in neurotransmitter release (13,14).…”
mentioning
confidence: 99%